THE EFFECT OF COMPOSITION OF MOCAF FLOUR AND YELLOW PUMPKIN ON CHARACTERISTICS NUGGET MOCAF YELLOW PUMPKIN - Putu Diartamasari Bendri; Anak Agung Nanak Antarini; Ni Nyoman Astika Dewi (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2020)
Pumpkin is an alternative to overcome malnutrition in Indonesia. Pumpkin can be processed into various kinds of processed foods to add nutritional value. Nugget is a processed chicken product that is printed, cooked, made from a mixture of ground chicken meat which is coated with or without the addition of other food ingredients and food additives that are allowed. Comparison of mocaf flour and pumpkin can add nutritional value to nuggets. This study aims to determine organoleptic characteristics including taste, aroma, color, texture, overall acceptance and texture quality on pumpkin mocaf nuggets, to determine the levels of β-carotene to the best pumpkin mocaf nuggets, and calculate the nutrient content produced in 1 portion of the best pumpkin mocaf nuggets. This study uses experimental methods with a type of Randomized Block Design (RBD). There are 5 treatments with a ratio of mocaf flour 85%, 80%, 75%, 70%, 65% and pumpkin 15%, 20%, 25%, 30%, 35%. Based on ANOVA, organoleptic quality nuggets for taste, aroma, and texture have a significant effect, color, overall acceptance and effect on texture quality is not significant. In 100 grams of pumpkin nuggets containing 2129.06 µg or equivalent to 177.41 RE. Nugget with the best characteristic is the ratio of 65% mocaf flour and 35% pumpkin.